The Crucial Roles of Phospholipids in Aging and Lifespan Regulation - Dai, Yucan; Tang, Haiqing; Pang, Shanshan (Frontiers in Physiology, 2021)
Phospholipids are major membrane lipids that consist of lipid bilayers. This basic cellular structure acts as a barrier to protect the cell against various environmental insults and more importantly, enables multiple cellular processes to occur in subcellular compartments. Numerous studies have linked the complexity of membrane lipids to signal transductions, organelle functions, as well as physiological processes, and human diseases. Recently, crucial roles for membrane lipids in the aging process are beginning to emerge. In this study, we summarized current advances in our understanding of the relationship between membrane lipids and aging with an emphasis on phospholipid species. We surveyed how major phospholipid species change with age in different organisms and tissues, and some common patterns of membrane lipid change during aging were proposed. Further, the functions of different phospholipid molecules in regulating healthspan and lifespan, as well as their potential mechanisms of action, were also discussed.